The physiological cost of velocity coupling during tennis groundstrokes - Cooke, K.; Davey, P. R. (Journal of Sports Sciences, 2007)
Velocity coupling denotes a perceptual motor behaviour known to occur during coincidence timing tasks. Individuals have been shown to increase their effector limb speed with increases in stimulus speed during interceptive tasks. However, little is known about the physiological effects of velocity coupling. The aim of this study was to determine the physiological cost of velocity coupling during tennis groundstrokes. Eight male and eight female competitive tennis players volunteered to perform three 4-min bouts of continuous groundstrokes against balls projected from a tennis ball machine at speeds of 18, 22, and 27 m/s (65, 79, and 97 km/h) and a frequency of 14 balls per minute, the order of which was counterbalanced. Breath-by-breath pulmonary gas exchange, heart rate, locomotion time, and limb acceleration were measured throughout each of the 4-min bouts. Capillary blood samples (for blood lactate analysis), rating of perceived exertion, and difficulty rating were taken at the end of each bout. Increasing ball speed did not influence the locomotion time between groundstrokes but did result in a bilateral increase in both the mean upper- and lower-limb acceleration (all P < 0.05). Velocity coupling behaviour increased oxygen uptake, blood lactate concentration, heart rate, rating of perceived exertion, and perceived task difficulty (all P < 0.05). It would appear, therefore, that velocity coupling influenced tennis groundstroke behaviour and indirectly modified the concurrent cardiopulmonary and metabolic responses.